Streptomyces nigra sp. nov. Is a Novel Actinobacterium Isolated From Mangrove Soil and Exerts a Potent Antitumor Activity in Vitro - Chen, Can; Ye, Yanghui; Wang, Ruijun; Zhang, Yinglao; Wu, Chen; Debnath, Sanjit C.; Ma, Zhongjun; Wang, Jidong; Wu, Min (Frontiers in Microbiology, 2018)
A new bacterial strain, designated 452T, was isolated from the rhizosphere soil of the mangrove Avicennia marina in China. As determined, its cell wall peptidoglycan contained LL-diaminopimelic acid; MK-9(H8) and MK-9(H6) were the major isoprenoid quinones; and iso-C16:0 (31.3%), anteiso-C15:0 (16.9%), and iso-C15:0 (12.5%) were the major cellular fatty acids (>10.0%). Phylogenetic analysis based on the 16S rRNA gene sequence revealed that strain 452T formed a distinct lineage in the clade of the genus Streptomyces, and was closely related to S. coerulescens DSM 40146T (99.6% sequence identity), S. bellus DSM 40185T (99.5%), and S. coeruleorubidus DSM 41172T (99.3%). The DNA-DNA relatedness between strain 452T and these type strains ranged between 29.3 and 42.3%. Based on the phenotypic, chemotaxonomic, and phylogenetic features, the strain 452T is considered to represent a novel species of the genus Streptomyces, for which the name Streptomyces nigra sp. nov. is proposed. The type strain is 452T (=KCTC 39960T=MCCC 1K03346T). Further, strain 452T extracts exhibited a pronounced antitumor activity against human cancer cell lines A549, HCT-116, and HepG2, but not against normal human colon cells CCD-18Co. Active substances in the fermentation broth of strain 452T were isolated by bioassay-guided analysis, and then purified using a macroporous resin, silica gel, sephadex LX-20 column, and semi-preparative high-performance liquid chromatography (HPLC). Eight proline-containing diketopiperazines, namely, cyclo(Pro-Ala), cyclo(Pro-Gly), cyclo(Pro-Phe), cyclo(Pro-Met), cyclo(Pro-Val), cyclo(Pro-Leu), cyclo(Pro-Tyr), and cyclo(L-Leu-trans-4-hydroxy-L-Pro), were identified by electrospray ionization mass spectrometry (MS) and nuclear magnetic resonance (NMR). The compounds displayed different levels of cytotoxicity. The highest cytotoxicity was exhibited by cyclo(Pro-Ala) and cyclo(Pro-Met) against A549 cells, and cyclo(Phe-Pro) and cyclo(Pro-Ala) against HCT-116 cells, with average IC50 values equal to 18.5, 27.3, 32.3, and 47.6 g/mL, respectively. The diversity of diketopiperazines and other chemicals produced by 452T was further investigated using gas chromatography (GC)-MS and liquid chromatography (LC)-MS. The analysis revealed 16 types of metabolites with antitumor activity and 16 other types of diketopiperazines. Hence, extracts of the newly identified strain may be used a starting material for the development of antitumor agents.